The Moderating Effects of Social Media Usage towards Fan Attachment in MotoGP - Zanuddin , Hasmah; Naufal Bin Yunos, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to investigate the relationships between MotoGP fans’ attachment to their favorite teams’ Facebook pages. Data were collected through survey method. The questionnaires were completed by 384 fans. Data were analyzed using the Statistical Package for the Social Sciences. Sports fans who have formed strong connections to their favorite team may be termed loyal fans. One popular communication tool for such fans is Facebook, which has been found to be an important medium for sharing news and events, yet few studies have examined the moderating of Facebook use in a sports context. Adopting the relational approach examining the determinants of sport-fan attachment, this study examined how Facebook use moderates the building of fan attachment. All independent variables together explain 78 percent of the variance (R Square) in Team Attachment, which is highly significant as indicated by the f values 336.845. Findings revealed the t-values of team attraction, social media, and team involvement are positively related to team attachment. Facebook use was found to significantly reinforce their attachment. Specific implications for both theory and practice are discussed. Overall, respondents indicated they preferred content related to players, including injury and movement, as well as race results, suggesting they might prefer using Facebook as another way to receive information instead of choosing to actively engage with their favorite team. However, because results from modeling suggest engaging individuals on Facebook has positive impacts on future behavioral intentions, sport marketers should consider engaging individuals on Facebook while still fulfilling their need for information about players and game results.